Shadow economy, tax morale, governance and institutional quality: a panel analysis - Benno Torgler; Friedrich G. Schneider (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper analyses how governance or institutional quality and tax morale affect the shadow economy, using an international country panel and also within country data. The literature strongly emphasizes the quantitative importance of these factors to understand the level and changes of shadow economy. However, the limited number of investigations use crosssectional country data with a relatively small number of observations, and hardly any paper has investigated tax morale and provides evidence using within country data. Using more than 25 proxies that measure governance and institutional quality we find strong support that its increase leads to a smaller shadow economy. Moreover, an increase in tax morale reduces the size of the shadow economy.
Keywords: D73; D78; H2; H26; O17; O5; 330; shadow economy; tax morale; governance quality; government intervention; corruption; Schattenwirtschaft; Steuermoral; Institutionelle Infrastruktur; Wirtschaftspolitik; Korruption; Schätzung; Welt